Strategi Komunikasi Bisnis yang Efektif dalam mengatasi Krisis - Arie Indra Chandra (Jurnal Administrasi Bisnis, 2010)
If the company fail to react proportionally when the crisis, then the situation mayworst, especially it will affect the image of the company. In the crisis, public willexamine closely whatever the company/management do. In this situation, the massmedia’s role in building the company image is very important. In the crisis, the managementshould govern the communication in three aspect, such as image building,mass media publication, dan public opinion. Understanding the public communication,particularly through the mass media is a great advantage in recovering thecompany reputation.Keywords: Business communication, communication strategy, mass media, publicopinion